PENGARUH BULLYING DALAM KOMUNIKASI INTERNAL TERHADAP KINERJA KARYAWAN DI PERUSAHAAN WISATA - Gusfa, Henni (MediaKom : Jurnal Ilmiah Komunikasi, 2016)
Abstract: Communication within an organization is very basic, but bad communication can damage the existing cultural order within an organization. Poor communication can cause bullying and have an impact on employee productivity. This study aims to determine how much influence bullying in internal communication on performance employee. Paradigm of research is positivistic and research method used is survey with quantitative approach. Data analysis method used is multiple linear regression. Furthermore, the object of his research is the employee of the South Jakarta Tourist Company, amounting to 55 employees taken with a sampling census. Result of t test calculation, the influence of internal communication (X1) on performance employee (Y) obtained count value tcount 4,707> 2,007 ttable with significance value 0.000 <0.005. The results of these calculations indicate that internal communication variables significantly affect the performance employee. Calculation with t test on variable bullying (X2), obtained tcount of 3,680> 2.007 table with significance value 0.001 <0.005. The results show that the variables of internal communication significantly affect the employee performance. Next with the F test, the Fcount value is 86.043 with a significance level of 0.000. It means that HO is rejected and Ha is accepted, since the value of Fcount is 86.043> 3.18 (Ftabel) and the significance value is 0.000 <0.05. So that can be stated internal communication and bullying effect simultaneously to performance employee. The magnitude of influence on the basis of the coefficient of determination of the two independent variables to the dependent variable is 0.768 or 76.8%. While the remaining 23.2% influenced by other variables that are not described in this study. Keywords: internal communication, bullying, employee performance